2020
DOI: 10.1093/eurheartj/ehz897
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and risk of incident arrhythmias in 402 406 individuals: evidence from the UK Biobank cohort

Abstract: Aims Physical activity reduces cardiovascular disease burden and mortality, although its relationship with cardiac arrhythmias is less certain. The aim of this study was to assess the association between self-reported physical activity and atrial fibrillation (AF), ventricular arrhythmias and bradyarrhythmias, across the UK Biobank cohort. Methods and results We included 402 406 individuals (52.5% female), aged 40–69 years, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 30 publications
2
90
0
1
Order By: Relevance
“…Given that CHD and AF share some common risk factors and the well-known inverse relationship between physical activity and CHD [6,7], one would expect that physical activity might have a beneficial effect on AF. Over the last decades, several reports have been published on the associations between physical activity and the risk of AF in the general population, but the results have been divergent; with some studies reporting decreased AF risk with regular physical activity [8][9][10] and others reporting an increased AF risk [11,12] or no evidence of an association. [13,14] Several meta-analyses have also been conducted in efforts to pool the existing evidence, but findings of these earlier reports have also been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Given that CHD and AF share some common risk factors and the well-known inverse relationship between physical activity and CHD [6,7], one would expect that physical activity might have a beneficial effect on AF. Over the last decades, several reports have been published on the associations between physical activity and the risk of AF in the general population, but the results have been divergent; with some studies reporting decreased AF risk with regular physical activity [8][9][10] and others reporting an increased AF risk [11,12] or no evidence of an association. [13,14] Several meta-analyses have also been conducted in efforts to pool the existing evidence, but findings of these earlier reports have also been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) reduces morbidity and mortality by reducing the burden of arrhythmias and improvement of cardiorespiratory fitness (CRF) through modulating lipid profiles, increasing aerobic capacities in adolescents, grown-ups and the elderly [3][4][5]. High-intensity interval (HIIT) and moderate continuous training (MCT) are established methods to preserve and boost endurance in professional and recreational sports as well as in patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity can enhance musclin expression in both muscles and the circulation, which improves exercise endurance (17). Some studies also reported that proper exercise could improve cardiorespiratory fitness in AF patients and prevent atrial and ventricular arrhythmias (18,38). Given this background, we speculated that decreased musclin levels would likely be involved in the occurrence and progression of AF.…”
Section: Discussionmentioning
confidence: 96%
“…A series of studies have reported the relationship of ANP or BNP with AF (12)(13)(14)(15), and NP has been recommended as a tool for the routine evaluation of patients with AF (16). Accordingly, physical exercise can up-regulate circulating musclin (17) and reduce the risk of atrial arrhythmias (18). However, musclin is found to increase insulin resistance in obesity (19) and vasoconstriction (20), which has been suggested to play a role in the onset of AF.…”
Section: Introductionmentioning
confidence: 99%